2008
DOI: 10.1051/0004-6361:200810565
|View full text |Cite
|
Sign up to set email alerts
|

The nearby eclipsing stellar systemδVelorum

Abstract: Context. The triple stellar system δ Vel system presents a significant infrared excess, whose origin is still being debated. A large infrared bow shock has been discovered using Spitzer/MIPS observations. Although it appears as a significant contributor to the measured IR excess, the possibility exists that a circumstellar IR excess is present around the stars of the system. Aims. The objective of the present VISIR and NACO observations is to identify whether one of the stars of the δ Vel system presents a cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
4
3
0
Order By: Relevance
“…This simple computation, however, does not take into account that the observer faces the coldest (equatorial) part of the system. The apparent magnitudes of the eclipsing pair synthesized by the ROCHE code (including all proximity effects and gravity darkening), U = 1.98 ± 0.02, B = 1.94 ± 0.02, V = 1.95 ± 0.02, and K = 1.86 ± 0.02 are in very good agreement with the observations: Kervella et al (2009) found V (Aab) = 2.00 ± 0.02 and K (Aab) = 1.86±0.09.…”
Section: The Triple System δ Velorumsupporting
confidence: 81%
See 3 more Smart Citations
“…This simple computation, however, does not take into account that the observer faces the coldest (equatorial) part of the system. The apparent magnitudes of the eclipsing pair synthesized by the ROCHE code (including all proximity effects and gravity darkening), U = 1.98 ± 0.02, B = 1.94 ± 0.02, V = 1.95 ± 0.02, and K = 1.86 ± 0.02 are in very good agreement with the observations: Kervella et al (2009) found V (Aab) = 2.00 ± 0.02 and K (Aab) = 1.86±0.09.…”
Section: The Triple System δ Velorumsupporting
confidence: 81%
“…The components are of similar temperature, however, both very probably being of spectral type A1V. This is strongly supported by a close agreement with the synthetic depth of the primary minimum in the K passband Δmag I = 0.430, while Kervella et al (2009) determined Δmag I = 0.440 ± 0.011 from the NACO imaging during the primary eclipse; -there is no apsidal motion in the system observed during the six-year time-series of the SMEI data as indicated by the observed times of the minima;…”
Section: Discussion and Future Worksupporting
confidence: 69%
See 2 more Smart Citations
“…The presence of interstellar material was also reported by Hempel & Schmitt (2003), who observed two red-shifted absorbing components in absorption in the Ca II K line of probably interstellar origin. In Paper I of the present series, Kervella et al (2009) confirmed that the infrared excess is essentially emitted by the bow shock, and not warm circumstellar material located close to the stars. In the framework of a search for resolved emission from debris disks, Moerchen et al (2010) obtained thermal infrared images of δ Vel using the Gemini South telescope and the T-ReCS instrument, and detected a marginally resolved emission at λ = 10.4 μm.…”
Section: Introductionsupporting
confidence: 74%